Konsep Wanprestasi dalam KHES dan KUH Perdata: Implementasinya di Pengadilan Agama - Larassati, Fiolenta (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2025)
The rapid growth of the sharia economy in Indonesia has raised challenges in resolving disputes in this field, especially related to breach of contract. Although the Compilation of Sharia Economic Law (KHES) has been established as a legal guideline for Religious Courts, judicial practice still often refers to the Civil Code (KUH Perdata), which is rooted in Western legal traditions. This study aims to analyze the breach of contract concept in the KHES and the Civil Code and its implementation in the decisions of the Religious Court. The method used is a juridical-normative approach with a deductive analysis of court decisions and related regulations. The results of the study show that there are inconsistencies in the implementation of KHES, which can have an impact on legal uncertainty. The implications of these findings emphasize the need to strengthen regulations and increase judge’s capacity to implement KHES to ensure legal certainty and justice in resolving sharia economic disputes.